2002
DOI: 10.1161/01.str.0000031928.71695.a9
|View full text |Cite
|
Sign up to set email alerts
|

Guglielmi Detachable Coil Embolization of Posterior Circulation Aneurysms

Abstract: Background-Early multicenter trials of Guglielmi detachable coil embolization of posterior circulations aneurysms have been followed by the publication of numerous single-center experiences. Summary of Review-We performed a MEDLINE literature search and extracted data from single-center reports containing at least 10 posterior circulation aneurysms. Twelve reports (495 aneurysms) were specific to the posterior circulation. Eighty-two percent of aneurysms arose near the basilar apex. Eighty-one percent of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 58 publications
6
53
0
1
Order By: Relevance
“…reported that patients with small posterior aneurysms have a mortality of 3% and a morbidity of 12.9%. Alan et al 9) . reported that 92.5% of patients treated with coiling for unruptured aneurysms in the posterior circulation achieve functional independence (Glasgow Outcome Scale 1 or 2), whereas only 1.9% ultimately live dependent lifestyles.…”
Section: Endovascular Coil Surgery In Aneurysms Of the Posterior Circmentioning
confidence: 99%
“…reported that patients with small posterior aneurysms have a mortality of 3% and a morbidity of 12.9%. Alan et al 9) . reported that 92.5% of patients treated with coiling for unruptured aneurysms in the posterior circulation achieve functional independence (Glasgow Outcome Scale 1 or 2), whereas only 1.9% ultimately live dependent lifestyles.…”
Section: Endovascular Coil Surgery In Aneurysms Of the Posterior Circmentioning
confidence: 99%
“…3,4,9 The introduction of detachable coils has greatly facilitated the management of basilar tip aneurysms, and coiling has rapidly replaced surgical treatment because coiling of basilar tip aneurysms is technically not different from coiling of aneurysms at other locations without additional associated morbidity. 5,8,10,20 Nowadays, surgical techniques for large and giant basilar tip aneurysms such as direct clipping under hypothermia with circulatory arrest and bypass surgery 18,19 are not serious treatment alternatives for coiling in most centers. Nevertheless, because most large and giant basilar tip aneurysms have a wide neck, coiling of these aneurysms may be technically difficult, and supporting devices that prevent coil herniation in the parent artery are frequently needed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] On the other hand, endosaccular occlusion of basilar tip aneurysms with detachable coils is relatively straightforward and not different from that in aneurysms at other locations. [4][5][6][7][8][9][10] Adjunctive supporting devices (supporting balloon, stent, or TriSpan [Boston Scientific, Fremont, Calif]) may facilitate coiling of wide-necked basilar tip aneurysms. [11][12][13] A drawback of coiling is the possibility of reopening of the aneurysmal lumen with time due to compaction of the coil mesh or migration of coils into intraluminal thrombus.…”
mentioning
confidence: 99%
“…1). (1)(2)(3)(4) In traditional craniotomy, an opening is made in the skull under general anesthesia, and the brain is gently retracted to locate the aneurysm. A neurosurgeon then places a tiny clip across the base, or neck, of the aneurysm to stop the blood flow into the aneurysm.…”
Section: Introductionmentioning
confidence: 99%